1988
DOI: 10.1002/chin.198831225
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Friedel‐Crafts Chemistry. Part 11. Boron, Aluminum, and Gallium Tris(trifluoromethanesulfonate) (Triflate): Effective New Friedel‐Crafts Catalysts.

Abstract: ChemInform Abstract The title compounds are prepared from the corresponding chlorides or BBr3 and CF3SO3H, isolated in pure form and fully characterized (elemental analysis, mol. wt., NMR and IR spectroscopy) (no yields given). B triflate is a monomeric, relatively volatile compound, whereas Al and Ga triflate are associated, high-melting solids. All three triflates are efficient new Friedel-Crafts catalysts as shown in alkylation, isomerization, and acylation reactions. Alkylation of benzene and toluene with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 1 publication
0
119
1
Order By: Relevance
“…For the formation of 5d , with an electron-neutral aryl group at the propargylic position, a higher catalyst loading and an elevated temperature were required in order to obtain high conversions. Phenol also reacted efficiently in a Friedel–Crafts-type reaction,17 to give para -substituted derivatives 5e – g exclusively. When using 2-phenylphenol as the nucleophile, the hydroxy group had a stronger directing power than the arene, as expected (Scheme 4, compound 5h ).…”
Section: Resultsmentioning
confidence: 99%
“…For the formation of 5d , with an electron-neutral aryl group at the propargylic position, a higher catalyst loading and an elevated temperature were required in order to obtain high conversions. Phenol also reacted efficiently in a Friedel–Crafts-type reaction,17 to give para -substituted derivatives 5e – g exclusively. When using 2-phenylphenol as the nucleophile, the hydroxy group had a stronger directing power than the arene, as expected (Scheme 4, compound 5h ).…”
Section: Resultsmentioning
confidence: 99%
“…Further study also showed that PPO can be depolymerised by copper-EDTA involving the redistribution mechanism in the ionic liquid ([emim][ABS]). 19 Our group has applied this depolymerisation and demonstrated that lignin can be successfully depolymerised using copper-EDTA as catalyst in both water and ionic liquids (1-ethyl-3- Some of these ligands, such as 1,1,4,7,7-pentamethyldiethylenetriamine (L1), tris(2-pyridylmethyl)amine (L2) 26 , and tris(2-Pyridylmethyl)amine (L3)…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The Friedel-Crafts reaction, i.e. the electrophilic attack of carbocations or related electrophiles at aromatic systems, 5 is one of the most useful CC bond-forming reactions in organic synthesis and many efforts have been devoted to the development of improved procedures for the catalytic Friedel-Crafts alkylations of indoles. 6 The large amounts of conventional Lewis acids usually required to promote typical Friedel-Crafts alkylation processes represent serious drawbacks (poor regioselectivities, undesired side-reactions of the electrophile, environmental concerns,…).…”
Section: Introductionmentioning
confidence: 99%